Social Portrait of a Student as a Component of Monitoring the Quality of the Organization of the Educational Process - A. A. Beschasnaya (Дискурс, 2019)
Introduction. Today, one of the criteria for assessing the quality of education is the opinion of students about educational services. Undergraduates enrolled in distance learning programs represent a specific student audience. Features of this category form a social portrait that has the information potential for organizing an effective educational process adapted to the “target audience”. Methodology and sources. In the academic year 2018–2019, the author conducted an empirical case study through an anonymous online survey of graduate students of the correspondence department of the first year of study. Results and discussion. As a result of the survey, respondents have received answers characterizing the peculiarities of their life, sociocultural environment, professional activity and factors of formation of motives of educational activity. The information obtained is presented in tables, which allowed to form a “numerical” outline of the social portrait of an extramural student. The result of an empirical study was a description of the collective image of a student studying in absentia in a magistracy. Active professional activity, focus on success, limited time resources, etc., determined the content of wishes for improving the conditions and process of educational activity. The main adjustments should relate to the effective planning of the educational process, methodological support of classroom and extracurricular activities, providing comfortable conditions for a long stay in an educational institution and communication with fellow students.Conclusion. The social portrait of students contains information about their typical representatives, the sociocultural environment of life.  Regular monitoring of the dynamics of socially significant characteristics of students allows you to quickly make adjustments that improve the quality of education.